2007
DOI: 10.1371/journal.pgen.0030192
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Independent Risk Factors for Lupus within the MHC in United Kingdom Families

Abstract: The association of the major histocompatibility complex (MHC) with SLE is well established yet the causal variants arising from this region remain to be identified, largely due to inadequate study design and the strong linkage disequilibrium demonstrated by genes across this locus. The majority of studies thus far have identified strong association with classical class II alleles, in particular HLA-DRB1*0301 and HLA-DRB1*1501. Additional associations have been reported with class III alleles; specifically, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
110
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(117 citation statements)
references
References 58 publications
5
110
1
1
Order By: Relevance
“…We observed some suggestive associations near HLA-B and -C and non-HLA genes (PZ1.37 Â 10 À 6 ) after conditioning on all HLA-DRB1 signals. This observation could be consistent with other fine-mapping studies that showed evidence of multiple independent associations in the MHC region [6][7][8][9] . Therefore, in the future, it is important to expand the same finemapping study on HLA alleles, HLA amino acids and SNPs with a larger sample size and multiple ancestral samples.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed some suggestive associations near HLA-B and -C and non-HLA genes (PZ1.37 Â 10 À 6 ) after conditioning on all HLA-DRB1 signals. This observation could be consistent with other fine-mapping studies that showed evidence of multiple independent associations in the MHC region [6][7][8][9] . Therefore, in the future, it is important to expand the same finemapping study on HLA alleles, HLA amino acids and SNPs with a larger sample size and multiple ancestral samples.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have attempted to dissect the SLE association within the extended MHC locus characterized by a high degree of linkage disequilibrium (LD) and genetic diversity [6][7][8][9][10] . Multiple HLA alleles and non-HLA variants in MHC locus have been suggested to have independent SLE-risk effects, as demonstrated by stepwise conditional analysis or HLA allele-allele haplotype analysis to control for the LD effect [6][7][8][9] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The particularly strong LD across these haplotypes has confounded attempts to identify clearly additional independent signals, such as those previously reported for complement C4-null alleles, as well as TNF and SKIV2L variants, all encoded within the class III region (19,32,33). The influence of copy number variation at the complement C4/RCCX locus in relation to the association signals demonstrated in this study remains to be established.…”
Section: Discussionmentioning
confidence: 70%
“…1 and Table S4). The analysis detected further associations in class III; hence there seem to be at least 3 separate signals in this region tagged by the SKIV2L gene, rs1269852, and NOTCH4 (19). Together, these data indicate the presence of multiple SLE risk alleles located across the class I, class II, and class III regions.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 71%